2013
DOI: 10.5558/tfc2013-033
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and lateral uprooting resistance of Salix matsudana Koidz in a riparian area

Abstract: Root morphological characteristics of Salix matsudana Koidz were studied using a complete excavation method. In-situ vertical and lateral uprooting tests were carried out on plants in a riparian zone to evaluate the soil-reinforcing ability of plant roots and flow resistance. Results show that the maximum uprooting force was positively correlated with stem basal diameter in both vertical and lateral uprooting tests. Resistance to uprooting was also significantly positively correlated with plant height, total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
5
1
0
Order By: Relevance
“…Correlation analyses of pullout resistance and morphological traits reveals a strong positive correlations with root collar diameter, root biomass and taproot length. These findings are consistent with the results of previous studies [56,62,63]. In general, tree roots play a vital role in shallow slope stabilization.…”
Section: Relationship Between Root Morphological Traits and Anchoragesupporting
confidence: 93%
“…Correlation analyses of pullout resistance and morphological traits reveals a strong positive correlations with root collar diameter, root biomass and taproot length. These findings are consistent with the results of previous studies [56,62,63]. In general, tree roots play a vital role in shallow slope stabilization.…”
Section: Relationship Between Root Morphological Traits and Anchoragesupporting
confidence: 93%
“…Regression analysis of uprooting force and growth characteristics shows strong positive correlations with height, root length, and root surface area. These results are congruent with previous studies [53,56,57]. In fact, V. rotundifoli with woody taproot and profuse lateral roots has higher uprooting resistance than I. pes-caprae and S. littoreus with fibrous roots.…”
Section: Plant Uprooting Resistancesupporting
confidence: 93%
“…In this study, results indicated that there was a moderate correlation between the maximum root pullout resistance and the height of C. korshinskii (r=0.599). This result was consistent with those of other plant species (Cucchi et al, 2004;Mickovski et al, 2005;Tanaka et al, 2011;Liu et al, 2013). In other words, the larger the plant, the higher its root pullout resistance (Liu et al, 2013).…”
Section: Variations Of Root Pullout Resistance and Plant Traits Of C ...supporting
confidence: 92%
“…This result was consistent with those of other plant species (Cucchi et al, 2004;Mickovski et al, 2005;Tanaka et al, 2011;Liu et al, 2013). In other words, the larger the plant, the higher its root pullout resistance (Liu et al, 2013). In addition, a moderate correlation between the maximum root pullout resistance and plant crown breadth (r=0.668) was obtained.…”
Section: Variations Of Root Pullout Resistance and Plant Traits Of C ...supporting
confidence: 90%